OP014 Analysis of 1792 gut metagenomes reveals microbial treatment targets for inflammatory bowel disease and irritable bowel syndrome. (16th January 2018) - Vich Vila, A; Imhann, F; Collij, V; Jankipersadsing, S A; Gurry, T; Mujagic, Z; Kurilshikov, A; Bonder, M J; Xiaofang, J; Tigchelaar, E; Dekens, J; Peters, V; et al.
Abstract: Background: Irritable bowel syndrome (IBS) and Inflammatory bowel disease (IBD) are two of the most common gastrointestinal disorders. The gut microbiome—the collection of microorganisms in the gut—presumably plays a large role in both diseases. Therefore, the microbiome holds great promise both as a diagnostic tool and as a target for treatment. However, thus far, functional studies have focused on single organisms whereas low-resolution microbial profiles based on marker genes (16S rRNA) have not been able to sufficiently understand the complex microbial changes in both diseases. In this study, we aim to bridge the gap between functional studies and 16S, by identifying complete species and functional gut microbiome profiles, using high-resolution shotgun metagenomic sequencing. Methods: We performed a large case–control study comprising stool samples of 1792 individuals: 355 IBD patients (comprising patients with Crohn's disease (CD) and ulcerative colitis (UC)), 421 IBS patients and 1025 population controls. Fecal DNA was isolated and sequenced generating 3.0 Gb of data per sample. In addition, a large number of phenotypes was collected for all participants, including lifestyle information and disease characteristics. Taxonomy, bacterial strain diversity and growth rates, gene families', virulence factors and antibiotic resistance protein abundances were inferred from the sequencing data. Results: Extensive multi-layer gut microbiome profiles were uncovered for both IBD and IBS. Interestingly, our results show a substantial overlap in microbial species alterations in patients with IBD and IBS compared with controls (83 taxa, FDR <0.1). The overlap included the decreased Faecalibacterium prauznitzii abundance in both IBD and IBS. In CD, not only the abundance, but also the strain diversity and the bacterial growth rate of Escherichia coli was increased. Interestingly, gut microbial characteristics were able to distinguish between IBD and IBS (AUC = 0.90), performing better than fecal calprotectin (AUC = 0.79). Bacterial virulence factors involved in mucosal damage and iron uptake were increased in patients with IBD. In addition, antibiotic resistances proteins, especially efflux pumps, were increased in both diseases. Large alterations in the microbial metabolic functions indicated that in CD an l -arginine deficiency, which is involved in wound healing, and vitamin B2 depletion, which acts as an anti-oxidant, could be targets for intervention. Conclusions: Using high-resolution microbial sequencing data of patients with IBD and patients with IBS, we identified microbial characteristics that can distinguish between these gastrointestinal diseases. Moreover, our comprehensive analysis identified several targets for microbial therapeutic trials.